The Effect of Investigation Through Cooperative Problem Solving (ITCPS) Learning Model on Students’ Activeness, Analytical Thinking Skills, and Science Learning Outcomes - Lafi Rusdiana; Budi Utami; Daru Wahyuningsih (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2026)
Students’ low activeness, analytical thinking skills, and science learning outcomes remain key challenges in lower secondary science learning when instruction provides limited opportunities for investigation, collaboration, and problem solving. This study examined the effect of the Investigation Through Cooperative Problem Solving (ITCPS) learning model on these three outcomes. A quasi-experimental method with a pretest-posttest nonequivalent control group design was used. The participants were 60 eighth-grade students at a middle school in Surakarta, Indonesia, consisting of 30 in the experimental class and 30 in the control class. The experimental class was taught using ITCPS, while the control class used Discovery Learning. Data were collected using an activeness observation sheet, an analytical thinking essay test, and a multiple-choice science learning outcomes test, then analyzed using descriptive statistics, assumption tests, and MANOVA. Results showed significant effects on activeness, F(1, 58) = 12.158, p = .001, partial eta squared = .173; analytical thinking skills, F(1, 58) = 9.023, p = .004, partial eta squared = .135; and science learning outcomes, F(1, 58) = 9.415, p = .003, partial eta squared = .140. The multivariate test also showed a significant simultaneous effect, with partial eta squared = .271. These findings indicate that ITCPS supports students’ active participation, analytical reasoning, and conceptual achievement in science learning.